PENERAPAN PIJAT TUINA DAN MINYAK SERAI DALAM MENURUNKAN NYERI DAN MENINGKATKAN KUALITAS TIDUR ANAK DENGUE HEMORRHAGIC FEVER - Lutfi, Lutfia Abdunisa; Hardini, Deisy Sri (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus transmitted through the bite of Aedes aegypti mosquitoes, which can induce fever. Tui Na massage is a potential alternative therapy with fewer side effects and economic burdens, offering greater flexibility for both parents and children to accept treatment. The purpose is to assess the pain intensity and improvement in sleep quality before and after Tui Na massage therapy. This study employed a single-case study research method in nursing science conducted from October 31 to November 2, 2023, at RSUD Banyumas. The results obtained were before therapy, Patient An. A frequently complained of pain, making sleep difficult. After receiving Tui Na massage and lemongrass aromatherapy oil for 15 minutes daily over three (3) days, there was a decrease in pain intensity and an improvement in sleep quality. Based on the results of the assessment, diagnosis, nursing care plan, impelentation adn evaluation as well as the application of evidence based practice, it was concluded that there was a reduction in pain intensity and an improvement in sleep quality following Tui Na massage therapy combined with lemongrass aromatherapy oil.